ANTONYM-BASED INTERJECTIONAL AND MODAL PHRASEOLOGICAL UNITS IN ENGLISH, UZBEK, AND RUSSIAN: A COGNITIVE AND FUNCTIONAL PERSPECTIVE (American Journal of Pedagogical and Educational Research, 2026)
This article examines phraseological units that incorporate antonymic components in English, Uzbek, and Russian, with a particular focus on their interjectional and modal functions. Rather than treating antonymy as a simple lexical contrast, the study approaches it as a dynamic mechanism that contributes to meaning extension, emotional intensity, and speaker stance. Drawing on comparative and qualitative analysis, the paper demonstrates that antonymic pairs within fixed expressions tend to lose their literal opposition and develop unified, often abstract meanings. At the same time, the study reveals both shared tendencies across languages and distinct language-specific patterns shaped by structural and cultural factors.